Comparative efficacy of Hormonal methods in oestrus synchronization and multiovulation in sheep - TAKARKHEDE, R C; KOLTE, A Y; PAWAR, R M (The Indian Journal of Animal Reproduction, 2023)
Studies were conducted at three different hormonal methods. 80 mg progesterone impregnated sponge for 14 days plus 1000 IU PMSG injection on sponge removal. 375 mg Progesterone implant subcutaneously for 14 days plus 1000 IU PMSG on day 12 of oestrus  cycle and 15 mg PGF2 alpha on day 14. Synchronization observed was 100, 85.71 and 100 percent respectively. In control group, it was 71.4 1 percent during entire period of cycle. The average time required for onset of oestrus after last hormonal injection w&s (46.28±9.5 hours) significantly longer than sponge and implant group. Duration of hormonaly synchronized oestrus in ewes of sponge group was (45.28±4.17 hours) significantly longer than implant group (33.00±2.58 hr) control group (28.2± 1.82 hours) and Prostaglandin group ( 40.00±3.45 hours). The average number of Carpora lutea was highly significant (P < 0.01) '.:>etween the sponge group and control group, implant group and control group, Prostaglandin group and control group. The difference was also highly significant (P < 0.01) between Prostaglandin group and sponge group. The average number of Carpora lutea were nonsignificant between sponge group and implant group.
Keywords: Hormonal method; oestrus synchronization; sheep